Impact of COVID‐19 in solid organ transplant recipients - Danziger‐Isakov, Lara; Blumberg, Emily A.; Manuel, Oriol; Sester, Martina (American journal of transplantation, 2021)
The coronavirus disease 2019 (COVID‐19) pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) exploded onto the world stage in early 2020. The impact on solid organ transplantation (SOT) has been profound affecting potential donors, candidates, and recipients. Importantly, decreased donations and the pressure of limited resources placed on health care by the pandemic also disrupted transplant systems. We address the impact of COVID‐19 on organ transplantation globally and review current understanding of the epidemiology, outcomes, diagnosis, and treatment of COVID‐19 in SOT recipients. The authors address the global impact of COVID‐19 on organ transplantation and the current understanding of the epidemiology, outcomes, diagnosis, and treatment of COVID‐19 in solid organ transplant recipients.